Cascade and anti-cascade+ production in central Pb+Pb collisions at 158 GeV/c per nucleon - Afanasiev, S.V (Array, 2003)
Results of the production of capital Xi, Greek- and Image hyperons are presented for the 10% most central Pb+Pb interactions at 158 GeV/c per nucleon where the average number of participants Npart is about 335. This analysis utilises a global reconstruction procedure, which allows a measurement of 4small pi, Greek integrated yields to be made for the first time. Inverse slope parameters, which are determined from an exponential fit to the transverse mass spectra, are found to be 267&plusmn ; ; ; ; 9 MeV and 296&plusmn ; ; ; ; 17 MeV for capital Xi, Greek- and Image hyperons, respectively. Mid-rapidity densities (dN/dy) are found to be 1.49&plusmn ; ; ; ; 0.08 and 0.33&plusmn ; ; ; ; 0.04 particles per event per unit rapidity for capital Xi, Greek- and Image, respectively. The ratio Image at mid-rapidity, R(y=ycm), is found to be 0.22&plusmn ; ; ; ; 0.03. Yields integrated to full phase space are found to be 4.12&plusmn ; ; ; ; 0.20 and 0.77&plusmn ; ; ; ; 0.04 particles per event for capital Xi, Greek- and Image hyperons, respectively.